Protective Effects of Sanyar Prebiotic on Immunity and Tissue Changes of Common Carp (Cyprinus carpio) Exposed to CuSO4 Stress - Ramezan Rajani; Mohammad Farhangi; Hojjatallah Jafaryan; Hossein Adineh; Maryam Alizadeh (Journal of Toxicology)
Prebiotics, as feed additives, can activate the antioxidant and immune systems of fish and significantly improve the survival of aquaculture animals in stressful conditions. The exposure of fish to copper sulfate leads to oxidative stress, suppression of the immune system, and destruction of vital body tissues. This study aimed to investigate the protective effects of Sanyar prebiotic on the immunity and tissue changes of common carp (Cyprinus carpio) exposed to CuSO4 stress. Two hundred common carp fish with an average weight of 12.33 ± 0.93 g were stocked in four treatments (triplicates) for 60 days. The experimental treatments contained Sanyar commercial prebiotics in 100 g of food, which included P1 (1 ml prebiotic liquid), P2 (0.1 g prebiotic powder), P3 (0.5 ml liquid and 0.05 g powder), and treatment C (control treatment without any additives). At the end of the experimental period, the fish were exposed to acute toxicity of Cu (0.1 m/l) for 96 hours. Gill, kidney, and liver tissue samples were collected and evaluated after 96 hours. According to the results obtained, there were significant differences in specific growth rate (SGR) and final weight (p < 0.05). The lowest feed conversion ratio (FCR) was observed in the Sanyar treatments (1.56 ± 0.37), which had a significant difference from the control treatment (1.85 ± 0.35) (p < 0.05). The results showed that immunity indices such as lysozyme, cortisol, and ACH50 increased in the experimental treatments compared to the control treatment (p < 0.05). The highest and lowest lysozyme activities were observed in P2 (16.35 ± 0.57) and control treatments (13.15 ± 1.00), respectively (p < 0.05). Generally, no significant difference was observed between growth and nutrition indices in Sanyar treatments (p < 0.05). Symptoms of kidney, liver, and gill tissue damage were reported from mild (hyperemia and infiltration of inflammatory cells) to severe (hemorrhage and necrosis). The lowest severity of tissue damage was observed in the treatments fed with Sanyar food supplement. In general, the results of this study showed that the addition of Sanyar prebiotic to the diet of common carp improves the growth indicators and immune response and can also be beneficial in increasing fish resistance to copper toxicity.